2013
DOI: 10.1002/jgrd.50431
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the melting layer on the passive microwave cloud scattering signal observed from satellites: A study using TRMM microwave passive and active measurements

Abstract: Concurrent passive and active microwave measurements onboard the Tropical Rainfall Measurement Mission (TRMM) show that under cloudy conditions, when a melting layer is detected by the precipitation radar, a polarized scattering signal at 85 GHz in passive mode is often observed. Radiative transfer simulations confirm the role of large horizontally oriented non‐spherical particles on the polarized scattering signal and assess the effect of changes in particle phase, from solid ice to dry snow to melting snow, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 46 publications
(80 reference statements)
3
25
0
Order By: Relevance
“…10a, implying that the melting layer in fact contributes partially to the PD signal. This finding is consistent with Galligani et al (2013), where they found that the 85 GHz PD of TRMM's TMI is likely positive when the melting layer is present. It is also consistent with the higher BB ZDR as observed by ground-based radars (e.g., Oue et al, 2015).…”
Section: Pds From Melting Layers and Ice Cloudssupporting
confidence: 89%
See 2 more Smart Citations
“…10a, implying that the melting layer in fact contributes partially to the PD signal. This finding is consistent with Galligani et al (2013), where they found that the 85 GHz PD of TRMM's TMI is likely positive when the melting layer is present. It is also consistent with the higher BB ZDR as observed by ground-based radars (e.g., Oue et al, 2015).…”
Section: Pds From Melting Layers and Ice Cloudssupporting
confidence: 89%
“…Galligani et al (2013) found that large 85 GHz PDs of TRMM-TMI were often associated with a melting layer underneath (detected by TRMM-PR), suggesting a strong connection between cloud ice processes and surface precipitation. Thus, we employ the GPM Ku-band radar bright band (BB) flag to evaluate the 89 and 166 GHz PD properties and their connection to the presence of BB, as BB is always associated with stratiform precipitation.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Polarized scattering signals from the frozen phase have been evidenced up to 90 GHz, from measurements with conical scanners such as the Special Sensor Microwave Imager or Tropical Rainfall Measurement Mission (TRMM) Microwave Imager (TMI) [ Prigent et al ., , ; Galligani et al ., ]. It has been shown that this polarized scattering can be explained by the interaction of the radiation with nonspherical and oriented particles and can bring insight into the cloud microphysics.…”
Section: Introductionmentioning
confidence: 98%
“…For spaceborne operations, it instead depends on the geometry: if the SCLW is above oriented particles, PD is reduced, while if it is below the ice layer, PD is actually enhanced (Xie et al 2015). Also the presence of a melting layer can lead to an increased PD (Galligani et al 2013;Gong and Wu 2017). IWP retrievals for current microwave satellite instruments exploiting the ice scattering signals for frequencies up to 190 GHz have been developed by Sun and Weng (2012), among others, for the Special Sensor Microwave Imager/Sounder (SSM/IS) and Surussavadee and Staelin (2009) for the Advanced Microwave Sounding Unit (AMSU)/ Microwave Humidity Sounder (MHS).…”
Section: Microwave Radiometers For Measurement Of Atmospheric Ice mentioning
confidence: 99%